PENERAPAN OUTDOOR LEARNING MELALUI IDENTIFIKASI KECERDASAN NATURALISTIK KEPADA SISWA KELAS V DI SDN PONDOK CABE ILIR 01 - Firsya Fimela Azzahra; Apri Utami Parta Santi; Azmi Al Bahij (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Outdoor Learning is a teaching method that involves students learning outside the classroom, utilizing the surrounding environment as a learning resource. This study aims to identify the implementation of outdoor learning through the naturalistic intelligence approach in fifth-grade students at SDN Pondok Cabe Ilir 01. Naturalistic intelligence refers to students' abilities to recognize, classify, and understand natural phenomena and interact with their environment. The research employs a qualitative approach with a descriptive design. Observations of outdoor learning activities conducted by teachers and interviews with students and teachers were used to understand the impact of outdoor learning on the development of students' naturalistic intelligence. The study subjects included 30 fifth-grade students and the teacher conducting the outdoor learning sessions. The results indicate that outdoor learning aligns well with students' naturalistic intelligence, especially in recognizing various types of plants, animals, and other natural phenomena. Activities such as direct observation of nature and group discussions facilitated students' environmental awareness and enhanced their critical thinking and teamwork skills. Based on these findings, it can be concluded that implementing outdoor learning has the potential to improve fifth-grade students' naturalistic intelligence at SDN Pondok Cabe Ilir 01, while also providing a more engaging and meaningful learning experience.